MELATONIN RECEPTOR GENE (MTNR1A) POLYMORPHISM AND ITS ASSOCIATION WITH AGE AT FIRST CALVING IN BUFFALOES - R.S. Kathiravan; R. Chitra; N. Murali; M. Arthanarieswaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A total of 203 blood samples were collected along with data on age at first calving from Murrah / graded Murrah buffaloes maintained at different organized farms. Genomic DNA isolation and Polymerase Chain Reaction (PCR) were performed to amplify the PCR products and were digested with HpaI restriction enzymes overnight. Population genetic indices was calculated based on basic statistical tools. At the MTNR1A / HpaI locus, three genotypes viz., CC, CT and TT identified, with frequencies of 0.225, 0.505 and 0.270 respectively. The allele frequencies of C and T alleles were 0.478 and 0.522 respectively. The overall means of age at first calving was 1385.76 ± 24.31 days. Individuals with the CT and TT genotypes (1356.78 ± 33.03 and 1378.38 ± 37.66 days) had shorter age at first calving than CC genotype (1422.14 ± 53.01 days) and the differences were statistically significant (P<0.05).